2012
DOI: 10.1111/j.1365-313x.2011.04850.x
|View full text |Cite
|
Sign up to set email alerts
|

ZINC TOLERANCE INDUCED BY IRON 1 reveals the importance of glutathione in the cross‐homeostasis between zinc and iron in Arabidopsis thaliana

Abstract: SUMMARYZinc is an essential micronutrient for plants, but it is toxic in excess concentrations. In Arabidopsis, additional iron (Fe) can increase Zn tolerance. We isolated a mutant, zinc tolerance induced by iron 1, designated zir1, with a defect in Fe-mediated Zn tolerance. Using map-based cloning and genetic complementation, we identified that zir1 has a mutation of glutamate to lysine at position 385 on c-glutamylcysteine synthetase (GSH1), the enzyme involved in glutathione biosynthesis. The zir1 mutant co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
91
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 86 publications
8
91
0
Order By: Relevance
“…S3; Fukao et al, 2011), which, in principle, would be sufficient to explain the subsequent induction of Fe deficiency-related processes. As reported previously (Fukao et al, 2011;Shanmugam et al, 2011Shanmugam et al, , 2012, foliar Fe supply strongly suppressed the development of chlorosis upon excess Zn (Fig. 6, A and B) and reduced shoot Zn accumulation to a certain extent (Supplemental Fig.…”
Section: Zn Strongly Induces Fe Deficiency Signaling and Related Physsupporting
confidence: 55%
“…S3; Fukao et al, 2011), which, in principle, would be sufficient to explain the subsequent induction of Fe deficiency-related processes. As reported previously (Fukao et al, 2011;Shanmugam et al, 2011Shanmugam et al, , 2012, foliar Fe supply strongly suppressed the development of chlorosis upon excess Zn (Fig. 6, A and B) and reduced shoot Zn accumulation to a certain extent (Supplemental Fig.…”
Section: Zn Strongly Induces Fe Deficiency Signaling and Related Physsupporting
confidence: 55%
“…In Arabidopsis thaliana, increased GSH levels were found to fortify oxidation tolerance to cadmium-and iron-mediated zinc stress (Maksymiec et al 2007;Shanmugam et al 2012;Sobrino-Plata et al 2014). It has been suggested that the activities of several antioxidant enzymes (GR and CAT) may be influenced by the transition between GSH and glutathione disulfide (GSSG) (Seth et al 2012).…”
Section: Detoxification Strategies In P Acerifoliamentioning
confidence: 97%
“…Arabidopsis (Arabidopsis thaliana) knockout mutants completely deficit in GSH biosynthesis show either embryo-or seedling-lethal phenotypes (Cairns et al, 2006;Pasternak et al, 2008), demonstrating its indispensable role in plant development. Other Arabidopsis mutants that have various degrees of reduction in endogenous GSH content show altered expression of stress-related genes (Ball et al, 2004;Mhamdi et al, 2010;Han et al, 2013aHan et al, , 2013b, enhancing sensitivity to excessive zinc (Shanmugam et al, 2012) and cadmium (Jozefczak et al, 2012) as well as pathogens (Parisy et al, 2007;Dubreuil-Maurizi and Poinssot, 2012).…”
mentioning
confidence: 99%